2021
DOI: 10.1053/j.ajkd.2021.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in Excess Deaths Among Persons With Kidney Failure During the COVID-19 Pandemic, March-July 2020

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…A combination of these health and socioeconomic factors may have resulted in increased vulnerability of Black populations relative to White populations early in the pandemic, contributing to the observed time trends. Prior evidence from persons with kidney failure is consistent with this theory: amongst this at-risk population, Black mortality exceeded White mortality by the largest margin early on in the pandemic (Kim et al, 2021). This mechanism would also be consistent with the relationship between the Black/White mortality ratio and changes in COVID-19 prevalence.…”
Section: Discussionsupporting
confidence: 66%
“…A combination of these health and socioeconomic factors may have resulted in increased vulnerability of Black populations relative to White populations early in the pandemic, contributing to the observed time trends. Prior evidence from persons with kidney failure is consistent with this theory: amongst this at-risk population, Black mortality exceeded White mortality by the largest margin early on in the pandemic (Kim et al, 2021). This mechanism would also be consistent with the relationship between the Black/White mortality ratio and changes in COVID-19 prevalence.…”
Section: Discussionsupporting
confidence: 66%
“…A combination of these health and socioeconomic factors may have resulted in increased vulnerability of Black populations relative to White populations early in the pandemic, contributing to the observed time trends. Prior evidence from persons with kidney failure is consistent with this theory: amongst this at-risk population, Black mortality exceeded White mortality by the largest margin early on in the pandemic [32] . This mechanism would also be consistent with a prevalence-disparity relationship.…”
Section: Discussionmentioning
confidence: 67%
“… 61 Another found that mortality among Hispanic patients with ESKD was 4-fold that of non-Hispanic patients. 62 A study by Hsu et al 63 based on patients from a midsize dialysis organization reported that male sex, Black race, treatment at an urban clinic, residence in a nursing home, and greater comorbidity burden were associated with COVID-19. Our results support these studies from the perspective of a national and more diverse chronic dialysis population.…”
Section: Discussionmentioning
confidence: 99%